Family Experience as Caregivers in the Rehabilitation of Stroke Patients: A Literature Review - Nurrandi, Sandra Ramadhanti; Kusuma Putri, Tri Antika Rizki (KnE Life Sciences, 2021)
This study aims to summarize the research results on family experiences as caregivers in post-stroke patients’ rehabilitation processes. The method of this study used a literature review. Google Scholar and PubMed were used to find Bahasa and English articles examining families as caregivers of stroke patients. These studies were assessed using the JBI critical appraisal tools for Qualitative Study with a total of 8 factors used to the quality of the selected articles. Nine articles were reviewed with JBI scores of about 90-100%. This study found 327 articles, and after quality assessment of these studies, nine articles came to review process. The review process generated six general aspects that have been summarized by researchers representing all emerging themes, namely physical, psychological, spiritual, economic, social, and family effort aspects. The results of this literature review hope can be a reference or provision related to families as caregivers. Keywords: caregiver, family, experience, stroke